Under my skin: Parenting behavior and children's cortisol in the Los Angeles family and neighborhood survey. Issue 4 (28th March 2022) - Tighe, Lauren A.; Birditt, Kira S.; Turkelson, Angela E.; Sastry, Narayan
Abstract: This study examined links between aspects of parenting behavior and children's cortisol and whether those links varied by child behavioral problems and ethnicity. Participants included children ages 9–15 ( N  = 159, 75% Latinx) and their primary caregivers from the Los Angeles Family and Neighborhood Survey (L.A.FANS; Wave 2). Children provided saliva upon waking, 30 min after waking, and at bedtime which was analyzed for cortisol. Analyses revealed associations between parenting behavior and cortisol were greater among children who had behavioral problems and these associations were stronger among non‐Latinx White children compared to Latinx children. This study moves beyond the current literature by investigating these important associations in a predominately Latinx urban sample of children.